2020
DOI: 10.1038/s41598-019-56621-6
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic interplay between pH and food resources affects copepod traits and performance in a year-round upwelling system

Abstract: Linking pH/pco 2 natural variation to phenotypic traits and performance of foundational species provides essential information for assessing and predicting the impact of ocean acidification (OA) on marine ecosystems. Yet, evidence of such linkage for copepods, the most abundant metazoans in the oceans, remains scarce, particularly for naturally corrosive Eastern Boundary Upwelling systems (EBUs). This study assessed the relationship between pH levels and traits (body and egg size) and performance (ingestion ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Three measurements were obtained per individual and averaged in the later analysis. While formalin is usually used to preserve plankton samples for length analysis (Connolly et al, 2017;Aguilera et al, 2020), previous work on zooplankton has shown no effect of ethanol preservation on body size (Black and Dodson, 2003) and any size effect would be consistent across the experiment. Further, ethanol preservation allows for downstream genetic analyses, which is essential when dealing with cryptic copepod species.…”
Section: Temperature Assaysmentioning
confidence: 95%
“…Three measurements were obtained per individual and averaged in the later analysis. While formalin is usually used to preserve plankton samples for length analysis (Connolly et al, 2017;Aguilera et al, 2020), previous work on zooplankton has shown no effect of ethanol preservation on body size (Black and Dodson, 2003) and any size effect would be consistent across the experiment. Further, ethanol preservation allows for downstream genetic analyses, which is essential when dealing with cryptic copepod species.…”
Section: Temperature Assaysmentioning
confidence: 95%
“…However, Pearson's analysis indicated population-specific phenotypic responses to local pH variations (Figure 4) that might reflect physiological to local scale pH conditions (Fitzer et al, 2012;Aguilera and Bednarsěk, 2022). Contradictory results have been found with regards to pH effects (null, positive, and negative) on Acartia species through in situ (Hansen et al, 2019;Aguilera et al, 2020b) or laboratory observations by means of short (day-week) to long term (transgenerational) experiments (Langer et al, 2019;Dam et al, 2021). This emphasized that both approaches are needed to draw more comprehensive patterns in the response of copepod species and related biological communities to climate change (Reum et al, 2016).…”
Section: Distribution Of Drivers and Copepod Traitsmentioning
confidence: 97%
“…This emphasized that both approaches are needed to draw more comprehensive patterns in the response of copepod species and related biological communities to climate change (Reum et al, 2016). In the case of copepod physiological responses to low pH, such interaction can be modulated if ample and nutritious food is available (Aguilera et al, 2020b;Cominassi et al, 2020), such as that observed in both coastal habitats. Significant correlations between EPR and field pH conditions might also correspond to the effect of other simultaneous environmental drivers affecting copepods physiology, including changes in temperature (Sasaki and Dam, 2019;Dam et al, 2021) and food spectra (Kleppel and Burkart, 1995;Jońasdottir et al, 2009).…”
Section: Distribution Of Drivers and Copepod Traitsmentioning
confidence: 99%